2021
DOI: 10.1002/adfm.202106923
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal Vacancy Manufacturing and Sodium‐Site Doping Enable a High‐Performance Layered Oxide Cathode through Cationic and Anionic Redox Chemistry

Abstract: Triggering the anionic redox chemistry in layered oxide cathodes has emerged as a paradigmatic approach to efficaciously boost the energy density of sodium-ion batteries. However, their practical applications are still plagued by irreversible lattice oxygen release and deleterious structure distortion. Herein, a novel P2-Na 0.76 Ca 0.05 [Ni 0.23 □ 0.08 Mn 0.69 ]O 2 cathode material featuring joint cationic and anionic redox activities, where native vacancies are produced in the transition-metal (TM) layers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 49 publications
0
85
0
Order By: Relevance
“…Since the electrolyte decomposes above 4.7 V (Figure S11b, Supporting Information), the oxidation/reduction peaks located at 2.6 V/2.4 V and 4.3 V/4.2 V are empirically assigned to the Mn 3+ /Mn 4+ and O 2-/O n− redox reactions, respectively, and the Ni 2+ /Ni 3+ /Ni 4+ redox reactions account for the peaks between 2.7 and 4.0 V (as will be confirmed in the following discussions). [17][18][19] Of note, the intensity of the Mn reduction peak at ≈2.4 V gradually increased while that of the O reduction peak at ≈4.2 V progressively decreased upon cycling, indicating the enhanced Mn and reduced O capacity contributions. This result is also verified by the discharge differential capacity (dQ/dV) curves in selected cycles (Figure 2b).…”
Section: Complementary Mn and O Redox Mechanism Upon Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the electrolyte decomposes above 4.7 V (Figure S11b, Supporting Information), the oxidation/reduction peaks located at 2.6 V/2.4 V and 4.3 V/4.2 V are empirically assigned to the Mn 3+ /Mn 4+ and O 2-/O n− redox reactions, respectively, and the Ni 2+ /Ni 3+ /Ni 4+ redox reactions account for the peaks between 2.7 and 4.0 V (as will be confirmed in the following discussions). [17][18][19] Of note, the intensity of the Mn reduction peak at ≈2.4 V gradually increased while that of the O reduction peak at ≈4.2 V progressively decreased upon cycling, indicating the enhanced Mn and reduced O capacity contributions. This result is also verified by the discharge differential capacity (dQ/dV) curves in selected cycles (Figure 2b).…”
Section: Complementary Mn and O Redox Mechanism Upon Cyclingmentioning
confidence: 99%
“…[6a] Noticeably, the discharge capacity of oxygen redox of NCLNM4 still remained after 30 cycles, whereas that of the nondoped NLNM sample disappeared after 15 cycles (Figure S19, Supporting Information), indicating the improved oxygen reaction reversibility after Na-site Ca doping (as is also evidenced by ex situ O 1s X-ray photoelectron spectroscopy (XPS), Figure S20, Supporting Information). [17] Figure 3c shows the cycling performance of the NCLNM samples at 0.1 C. Compared with the NCLNM5 and NCLNM3 electrodes, the NCLNM4 cathode delivers a superior overall performance in terms of a desirable discharge capacity of 136.9 mAh g -1 and a high capacity retention of 94.2% after 50 cycles. This is due to the appropriate balance between the TM-vacancy concentration and Ca 2+ doping, and the excellent cycling stability of NCLNM4 could be further attributed to the complementary mechanism.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…This synergic effect leads to a smooth voltage profile and a solid-solution phase transition over 1.5−4.5 V (Figure 6b). Similarly, Shen et al [72] T A B L E 1 Summary of current Na-based layered cathode materials with elemental doping/substitution. | 79 reported that the synergic effects of intrinsic TM vacancies and Ca 2+ located at the Na site can also enhance the anionic reversibility and lead to a reversible P2−OP4 phase transition rather than the irreversible P2−O2 phase transition (Figure 6c).…”
Section: Metallic Elemental Doping/ Substitutionmentioning
confidence: 99%
“…Reproduced with permission: Copyright 2021, Wiley-VCH. [72] TM layer (1450 ppm peak in 7 Li pjMATPASS NMR spectra, MAT = magic-angle turning, PASS = phase-adjusted sideband separation, and pj = projection) seems to be sufficient to maintain the structural stability and eliminate the O2−P2 phase transition during cycling even upon charging to 4.5 V. [126] Peng et al [98] realized site-selective doping of a P2type layered cathode with a Cu ion at the TM site (2a) and Zn 2+ at the Na site (2d) for the first time. Cu 2+ doping at the TM site can stabilize the TM layer, and the Zn 2+ at the Na site can enhance the electrostatic cohesion between two adjacent TM layers, changing the phase transition from an irreversible P2−O2 phase to a reversible P2−Z phase.…”
Section: Codoping/cosubstitutionmentioning
confidence: 99%
See 1 more Smart Citation